2003
DOI: 10.1055/s-2003-43110
|View full text |Cite
|
Sign up to set email alerts
|

Behandlung von Patienten mit chronischen lumbalen Rückenschmerzen in einem Ergonomietrainingsprogramm: Wie verändern sich arbeitsbezogene Funktionsparameter, Schmerzparameter und die Arbeitstätigkeit nach 12 Monaten?

Abstract: ZusammenfassungFragestellung: Welchen Einfluss hat ein stationäres funktionsorientiertes Ergonomietrainingsprogramm (ETP) mit dem Ziel, die arbeitsbezogene Leistungsfähigkeit zu verbessern, auf verschiedene Schmerz-und Funktionsparameter? Wie groû ist der prädiktive Wert von verschiedenen klinischen Tests für das Rehabilitationsresultat? Methode: Prospektive Kohortenstudie mit 6-und 12-Monats-Nachkontrollen. Bei Eintritt und Austritt wurden die Schmerzintensität und -lokalisation, die Hebeleistung, die max. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This is not only due to the time-consuming nature of some of these assessments but also to its perceived limited evidence for predictive value regarding work participation. Regarding the time-consuming nature, this study also showed that a number of tests were predictive of work participation: lifting tests (Gross et al 2004; Gross and Battié 2005, 2006; Gouttebarge et al 2009a; Hazard et al 1991; Matheson et al 2002; Strand et al 2001; Vowles et al 2004), a 3-min step test and a lifting test (Bachman et al 2003; Kool et al 2002), a short-form FCE consisting of tests specific for the region of complaints (Gross and Battié 2006; Branton et al 2010), and a trunk strength test (Mayer et al 1986). A performance-based lifting test was most often used and appeared to be predictive of work participation in 13 of these 14 studies—especially a lifting test from floor-to-waist level in patients with chronic low back pain.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…This is not only due to the time-consuming nature of some of these assessments but also to its perceived limited evidence for predictive value regarding work participation. Regarding the time-consuming nature, this study also showed that a number of tests were predictive of work participation: lifting tests (Gross et al 2004; Gross and Battié 2005, 2006; Gouttebarge et al 2009a; Hazard et al 1991; Matheson et al 2002; Strand et al 2001; Vowles et al 2004), a 3-min step test and a lifting test (Bachman et al 2003; Kool et al 2002), a short-form FCE consisting of tests specific for the region of complaints (Gross and Battié 2006; Branton et al 2010), and a trunk strength test (Mayer et al 1986). A performance-based lifting test was most often used and appeared to be predictive of work participation in 13 of these 14 studies—especially a lifting test from floor-to-waist level in patients with chronic low back pain.…”
Section: Discussionmentioning
confidence: 62%
“…The other five studies used tests or combinations of like a step test, a lift test, or a trunk strength tester. Two studies combined the results of the performance-based test with non-performance-based outcomes like pain and Waddell signs (Bachmann et al 2003; Kool et al 2002). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations